Mental Health of Early and Prolonged Parent–Child Separated Children in Chinese Immigrant Families: A Qualitative Study With Parent–Child Dyads - Weiyi Sunny Fu; Risa Yokoyama; Xihan Yang; Jian (Lily) Chen; Shaobing Su (Child & Family Social Work, 2026)
ABSTRACT Parent–child separation is a global crisis that has affected child and family health and well‐being. Many Chinese immigrant families in the US practice early and prolonged parent‐child separation (EPPCS), sending US‐born infants to China for extended family care and reuniting them around school age. However, little research has explored child mental health post‐reunification, especially based on parent–child dyad reports. The present qualitative study explored child mental health based on key informative interviews from affected children (ages 12–17) and their primary caregivers ( N = 24 parent–child dyads; N girls = 12; mean child age = 14.25; N mothers = 22), aiming to understand the potential impact of separation and inform future mental health research and services for these children. Results indicated that separated‐reunited children exhibited negative outcomes such as avoidance of disclosure of mental health challenges, social withdrawal, externalized problems, internalized problems and low‐quality sleep. Some children also exhibited positive mental health conditions such as a positive perception of general mental health, high self‐esteem, healthy social engagement and high‐quality sleep. These findings indicate mental health disparities within this group and highlight the need to investigate risk and protective factors that may contribute to these disparities. Tailored interventions are needed, especially for those facing serious mental health issues.